Aspronema cochabambae (Squamata: Lacertilia: Scincidae): its discovery in Argentina, morphological variation and extent of suitable habitat - Burgos Gallardo, Freddy (2019)
As currently defined, the genus Aspronema Hedges & Conn, 2012 contains two species, A. cochabambae (Dunn, 1935) and A. dorsivittatum (Cope, 1862) (Hedges & Conn 2012). The latter species is widely distributed in Bolivia, Brazil, Paraguay Uruguay, and Argentina. In Argentina, A. dorsivittatum occurs in Chacoan grasslands and forests below 1,200 m a.s.l., yet has been poorly sampled (Cei 1993, Avila et al. 2013).